2023
DOI: 10.1200/jco.22.00838
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Fight: Why President Biden's Cancer Moonshot Must Include Palliative Care

Abstract: Author affiliations and support information (if applicable) appear at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Moreover, studies have shown that palliative care can lengthen survival when integrated early into the care of some patients with cancer. Without sufficient inclusion of palliative care and cancer survivorship in the Moonshot initiative, many patients, especially those facing the ends of their lives and long‐term survivors, will miss out on its benefits 13 . Distinct efforts will be required for childhood cancer survivors, who often face unique long‐term challenges.…”
mentioning
confidence: 99%
“…Moreover, studies have shown that palliative care can lengthen survival when integrated early into the care of some patients with cancer. Without sufficient inclusion of palliative care and cancer survivorship in the Moonshot initiative, many patients, especially those facing the ends of their lives and long‐term survivors, will miss out on its benefits 13 . Distinct efforts will be required for childhood cancer survivors, who often face unique long‐term challenges.…”
mentioning
confidence: 99%